Impulsiveness and cognitive patterns. Understanding the perfectionistic responses in Spanish competitive junior athletes - González-Hernández, J.; Capilla Diaz, C.; Gómez-López, M. (Frontiers in Psychology, 2019)
Introduction: High performance sport requires that the athletes maintain a constant intensity and control of their personal resources, as well as a balance between self-regulation and performance. Likely, such requirements involve the influence of their beliefs regarding the tasks to be performed to improve the confidence in their own resources to face the competition. Theoretical arguments provide new insights for understanding multidimensional perfectionism and its relationships with other variables such as affective experiences, among others. In this study, perfectionism was conceptualized as a "stable personality disposition," whereas the impulsiveness components were defined as "representing psychological mechanisms (or processes)" underlying the relationships between perfectionism and athletic experiences.